POLITIK HUKUM BELA NEGARA DALAM PERSPEKTIF PERTAHANAN NEGARA - Muhammad Nakir (Pascasarjana Ilmu Hukum, Universitas Widyagama Malang, 2017)
Awareness of state defenses has been mandated in Article 27 verse (3) of the 1945 Constitution of the Republic of Indonesia. Ideally, defending the state as part of the state defense becomes a decisive factor in ensuring the survival of the nation and the state. The state will not be able to maintain its existence without the citizens’ support. But in reality, these fundamental interests are not always facilitated by the regulation of legal products, since the law can not be separated from the political influence. The political configuration of each era from the Old Order Era to the Reform Era shows the tug of government’s commitment to legislation on state defense. Keywords: Political Law, State Defense, State Defense.